Moving Beyond 100 Years: The "WA Approach" to National Party Survival - Phillimore, John; McMahon, Lance (Wiley-Blackwell Publishing Asia, 2015)
Since its formation in 1913, the Western Australian branch of the National Party has faced many challenges to its survival. Electoral reform removing rural malapportionment in 2005 prompted changes in strategic direction, including abandoning coalition with the Liberal Party and creating a discrete image, branding and policy approach. Holding the balance of power after the 2008 election, the party adopted a post-election bargaining strategy to secure ministries and funding for its "Royalties for Regions" policy. This "WA approach" is distinctive from amalgamation and coalition arrangements embraced elsewhere in Australia. This article updates progress of the strategy following state and federal elections in 2013 and finds that it has been a success measured by increased votes, seats and policy influence and expansion into regional Western Australia to displace Labor. However, its applicability to other branches of the National Party is likely to be limited.